Acute Vision Loss as the Initial Manifestation of Granulomatosis with Polyangiitis Involving the Orbital Apex - Shang-Yen Wu; Ling-Shuo Chang; Yuan-Chieh Lee; Yu-Jen Pan; Yu-Fu Chou; Fang-Ling Chang; Yu-Hsuan Lu; Nancy Chen (Diagnostics, 2022)
Granulomatosis with polyangiitis (GPA) is a systemic autoimmune disease consisting of necrotizing granulomatosis of the respiratory tract, necrotizing vasculitis, and necrotizing glomerulonephritis. It is under the category of ANCA-associated vasculitis, which involves small vessels. The nose, sinus, and ear were the most affected sites besides lung and kidney in localized form. They might precede other disease manifestations before progressing to the systemic form. Our patient presented with an intractable headache, followed by acute vision loss. His symptoms deteriorated regardless of antibiotic treatment for paranasal sinusitis. The sequential CT/MRI images showed the inflammatory raid of the orbital apex and cavernous sinus within days. The sinus biopsy and elevated PR3-anti-neutrophil cytoplasmic antibody led us to the diagnosis of GPA. Fortunately, the patient’s vision improved gradually after steroid and immunosuppressant treatment.